1998
DOI: 10.1152/jappl.1998.84.6.1827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arterial occlusion on responses of group III and IV afferents to dynamic exercise

Abstract: Our laboratory has shown previously that a low level of dynamic exercise induced by electrical stimulation of the mesencephalic locomotor region (MLR) stimulated group III and IV muscle afferents in decerebrate unanesthetized cats (C. M. Adreani, J. M. Hill, and M. P. Kaufman. J. Appl. Physiol. 83: 1811-1817, 1997). In the present study, we have extended these findings by examining the effect of occluding the arterial supply to the dynamically exercising muscles on the afferents' responses to MLR stimulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
100
1
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 16 publications
1
100
1
4
Order By: Relevance
“…most part confirmed these findings. In addition, the present study has shown for the first time that postexercise circulatory occlusion, a maneuver that was not performed in our previous studies (1,2,25), significantly increased over (preexercise) baseline levels the discharge of group IV, but not group III, afferents.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…most part confirmed these findings. In addition, the present study has shown for the first time that postexercise circulatory occlusion, a maneuver that was not performed in our previous studies (1,2,25), significantly increased over (preexercise) baseline levels the discharge of group IV, but not group III, afferents.…”
Section: Discussionsupporting
confidence: 46%
“…We (1,2,25) have shown previously that dynamic exercise increased the activity of group III and IV afferents in decerebrated cats. This increase displayed two characteristics.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The former involves muscle metaboreceptor and mechanoreceptor afferent signals integrated at the level of the hypothalamus or medulla oblongata, while the latter involves integration of the two afferents (e.g., sensitization) at the activating muscle level (1,30). When muscle mechanoreceptors and metaboreceptors are activated in the same muscle, both central and peripheral integration would induce physiological responses.…”
mentioning
confidence: 99%
“…However, although injection of an acid solution can stimulate both the group III and IV muscle afferent fibres, there is still no evidence that relatively small changes in muscle pH, such as those resulting from the Haldane effect in fluid with a high buffering capacity, could represent a source of stimulation of these thin muscle afferents during an exercise of light or moderate intensity. For instance, complete occlusion of the hindlimb circulation seems to have a very small stimulatory effect on muscle group IV, and no effect on group III, endings of the triceps in the cat during walking (Adreani & Kaufman, 1998). Moreover, since the study by Dejours et al (1955), there have been consistent reports that trapping all the metabolic-like products of exercise -including H¤ -in the post-exercising muscles does not stimulate ventilation.…”
Section: Mechanisms Of Oµ-induced ýE Stimulation During Exercisementioning
confidence: 95%